Ihtibak in Al-Biqa'i’s Exegesis of Surah Yasin: ‎ A Theoretical and Applied Study ‎ - Abdul Wahab Almunawar; syafruddin syafruddin; Toni Markos; Sesra Ayu Ningsih (Jurnal Ulunnuha, 2025)
The concept of al-Ihtibak according to al-Biqa’i indicates the presence of intertwined structures in sentences, where one structure refers to a statement without the need for repetition in the other. Al-Biqa’i adopts a different explanatory approach, considering verses containing "al-Ihtibak," interpreting the components, meanings, and mysteries in various ways. He categorizes "al-Ihtibak" into three patterns and presents five different types of it. In his analysis of Surah Yasin, he applies "al-Ihtibak" to specific six verses to expand and enhance their meanings more accurately and concisely. The researcher provides a descriptive analysis of "al-Ihtibak" with illustrative tables, highlighting the wisdom of "al-Ihtibak" in clarifying the purposes of the Quran and making expression concise and adorned.